1992
DOI: 10.1002/jmv.1890380110
|View full text |Cite
|
Sign up to set email alerts
|

Sexual transmission of human T‐lymphotropic virus type I in Peruvian prostitutes

Abstract: The epidemiology of HTLV-I infection in female prostitutes was studied in a survey of 395 prostitutes from Callao, Peru (the port city of Lima), 72 prostitutes from Iquitos, Peru (another port city on the Amazon River), and 510 prenatal clinic patients from Lima. Prostitutes reported a mean of 8.8 years (range, 1-39 years) of active prostitution and a mean of 205 sexual contacts during the month prior to the study. The percentage of prostitutes with HTLV-I antibody (21.8%) was significantly higher than patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1
10

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 24 publications
0
28
1
10
Order By: Relevance
“…Wignall et al 62 reported a 21.8% prevalence rate of HTLV-1 among prostitutes in Callao, Peru, which was correlated with the number of years of prostitution; this fi nding suggests an association between sexual activity and HTLV-1 transmission. Nakashima et al 58 found a signifi cantly higher prevalence of anti-HTLV-l antibodies (5.1%) in 409 female prostitutes in Kyushu, Japan than in a control group of non-prostitutes (1.3%).…”
Section: Sexual Transmissionmentioning
confidence: 96%
See 1 more Smart Citation
“…Wignall et al 62 reported a 21.8% prevalence rate of HTLV-1 among prostitutes in Callao, Peru, which was correlated with the number of years of prostitution; this fi nding suggests an association between sexual activity and HTLV-1 transmission. Nakashima et al 58 found a signifi cantly higher prevalence of anti-HTLV-l antibodies (5.1%) in 409 female prostitutes in Kyushu, Japan than in a control group of non-prostitutes (1.3%).…”
Section: Sexual Transmissionmentioning
confidence: 96%
“…In addition, the epidemiology of HTLV, particularly its tendency to occur in clusters, has enabled the identifi cation of groups who are at risk for exposure, including injection drug users 34,56,59 , sex workers 50,[55][56][57][58][59][60][61][62] , men who engage in intercourse with other men 52,53,56 , recipients of blood transfusions in Brazil before November 1993 63 , and sexual partners of known HTLV carriers [64][65][66] (Figure 2). …”
Section: Sexual Transmissionmentioning
confidence: 99%
“…La prevalencia de infección por el HTLV-1, otro retrovirus cuya forma de transmisión es similar a la de VIH y que en infección dual con el mismo empeora el pronóstico del SIDA (27,28), se encontró en una proporción similar al encontrado en 1990 (19), pero menor al 7% encontrado por Gotuzzo (25), en 1992 en meretrices registradas y clandestinas de Lima, y al 25% encontrado por Wignall y col. (29), en 1989 en meretrices registradas del Callao. Sin embargo hay que tener en cuenta que nuestra población es más joven y trabajan como meretrices menos años.…”
Section: Discusionunclassified
“…Quechuas, Mestizos, Blacks), and groups with risky sexual behavior (e.g. commercial sex workers) 20,23,24 . HIV/HTLV-I co-infection has previously been reported in Peru, and a shorter survival after onset of clinical acquired immunodeficiency syndrome (AIDS) was described in co-infected men 16 .…”
Section: Introductionmentioning
confidence: 99%